DETERMINING PREVALENCE, RISK OF PRESSURE ULCERS IN PATIENTS AFTER CRANIOTOMY AT THE ANESTHESIA AND INTENSIVE CARE CENTER, BACH MAI HOSPITAL, 2025 (Vietnam Journal of Community Medicine, 2026)
Objects: Assessment of the current status, pressure ulcer risk in patients after craniotomy at the Anesthesia and Intensive Care Center, Bach Mai HospitalMethods: A cross-sectional descriptive study involving 281 post-craniotomy patients at the Anesthesia and Intensive Care Center, Bach Mai Hospital, 2025.Results: The mean Braden score for pressure ulcer risk was 15.01 ± 2.90. The risk distribution was as follows: 14.59% had no risk, 34.16% low risk, 30.96% moderate risk, 19.22% high risk, and 1.07% very high risk. The incidence of new pressure ulcers after surgery was 29.89%, with all lesions classified as stage I-II, typically occurring within 4-14 days postoperatively. The most common ulcer sites were the flank, sacrum, heel, occiput, and back.Conclusion: Patients after craniotomy have a high risk of developing pressure ulcers, with a new incidence of nearly 30%, mainly at stages 1-2 and concentrated in pressure-prone areas such as the flank, sacrum, and heel. This study provides specific data for the neuro-critical care patient group, contributing practical evidence on the pathogenesis and guiding preventive strategies.
Keywords: Presure ulcer, situation, risk, postsurgery, craniotomy.